2015
DOI: 10.1007/s11136-015-1108-2
|View full text |Cite
|
Sign up to set email alerts
|

Japanese population norms for preference-based measures: EQ-5D-3L, EQ-5D-5L, and SF-6D

Abstract: PurposeThe purpose of this study was to measure the population norms for the Japanese versions of preference-based measures (EQ-5D-3L, EQ-5D-5L, and SF-6D). We also considered the relations between QOL score in the general population and socio-demographic factors. MethodsA total of 1143 adult respondents (aged ≥ 20 years) were randomly sampled from across Japan using data from the Basic Resident Register. The health status of each respondent was measured using the EQ-5D-3L, EQ-5D-5L, and SF-6D, and responses r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

40
172
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 256 publications
(221 citation statements)
references
References 54 publications
40
172
4
Order By: Relevance
“…In addition, this study revealed that sex, years of schooling, and chronic diseases were strongly associated with QoL. A similar study [24] showed that females, lower education, unemployment, and hospitalization due to diabetes and side effects of the disease were correlated with lower QoL and reporting some or extreme problems in various dimensions. Moreover, the difference in QoL scores between people with and without any disease was approximately 0.064, which is less than what we found (0.119).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…In addition, this study revealed that sex, years of schooling, and chronic diseases were strongly associated with QoL. A similar study [24] showed that females, lower education, unemployment, and hospitalization due to diabetes and side effects of the disease were correlated with lower QoL and reporting some or extreme problems in various dimensions. Moreover, the difference in QoL scores between people with and without any disease was approximately 0.064, which is less than what we found (0.119).…”
Section: Discussionsupporting
confidence: 61%
“…Our results also showed that no significant difference was found in QoL according to insurance type, complementary insurance, or smoking status. Similar to our study, the causal relationship between income and health status was not clear, but this information may be very valuable for policymakers nonetheless [24]. …”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…EQ‐5D™ scores characterized each assessment after baseline as improved or deteriorated if the score changed by at least 0·05 points, and stable if it changed by less than 0·05 points21, 22, 23.…”
Section: Methodsmentioning
confidence: 99%